The Contribution of Serum Complement Component 3 Levels to 90-Day Mortality in Living Donor Liver Transplantation - Fukui, Saeko; Hidaka, Masaaki; Fukui, Shoichi; Morimoto, Shimpei; Hara, Takanobu; Soyama, Akihiko; Adachi, Tomohiko; Matsushima, Hajime; Tanaka, Takayuki; Fuchigami, Mai; Hasegawa, Hiroo; Yanagihara, Katsunori; et al. (Frontiers in Immunology, 2021)
The contributions of the complement system have been elucidated in the process of solid organ transplantation, including kidney transplantation. However, the role of complement in liver transplantation is unknown. We sought to elucidate the time-dependent changes of peritransplantational serum complement levels and the relationships with posttransplant outcomes and other immunological biomarkers. We enrolled 82 patients who underwent living-related donor liver transplantation (LDLT). Nine patients (11%) died within 90 days after LDLT (non-survivors). The following immunomarkers were collected preoperatively and at 1, 2, and 4 week(s) after LDLT: serum C3, C4, immunoglobulin G (IgG), and peripheral blood leukocyte populations characterized by CD3, CD4, CD8, CD16, CD19, CD20, CD22, and CD56. Consequently, C3 and C4 increased time-dependently after LDLT. Preoperatively, C3 was negatively correlated with the MELD score, Child–Pugh score, CD16-positive leukocyte percentage, and the CD56-positive leukocyte percentage. Non-survivors had lower levels of C3 at 2 weeks in comparison to survivors (median [interquartile range]: 56 [49-70] mg/dL vs. 88 [71-116] mg/dL, p=0.0059). When the cutoff value of C3 at 2 weeks to distinguish non-survivors was set to 71 mg/dL, the sensitivity, specificity, and area under the ROC curve were 87.5%, 75.0%, and 0.80, respectively. A principal component analysis showed an inverse relationship between the C3 and C4 levels and the percentage of CD8-, CD16-, and CD56-positive leukocytes at 1 and 2 week(s). All non-survivors were included in the cluster that showed higher percentages of CD8-, CD16-, and CD56-positive leukocytes at 2 weeks. In conclusion, we demonstrated the relationship between complement, outcomes, and other immunomarkers in LDLT and suggested the usefulness of C3 at 2 weeks after LDLT in distinguishing the mortality.